Promising Breeds And Hybrids Of Silkworms For The Introduction Of Sericulture Karakalpakstan (Texas Journal of Agriculture and Biological Sciences, 2024)
Breeds from the world collection of silkworms of the NIIS, marked by sex at the grenadian stage and distinguished by high biological indicators, can be used to create 100% pure hybrids.